A urological challenge: Voiding dysfunction in multiple sclerosis - Corcos, Jacques (Canadian Urological Association Journal, 2013)
Patients with multiple sclerosis (MS) have a very high prevalence of lower urinary tract symptoms—as many as 90% of patients with MS experience some form of voiding dysfunction and/or incontinence.1 This summary provides a brief overview of MS epidemiology, pathophysiology, the impact of the disease on patient quality of life, and the particular kinds of urinary tract abnormalities and symptoms that can present among patients with MS. Strategies to help diminish the impact of these symptoms are also discussed.